The Importance and Potential of Mafic Dyke Swarms in Studies of Geodynamic Processes - Halls, H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Summary Mafic dykes from North America and India are used to highlight certain structural features that may provide further insight into the origin and geodynamic significance of dyke swarms, particularly those of Precambrian age. Structural aspects of interest within any one swarm include regional variations in dyke attitude, perference in direction of dyke branching, radiating dyke patterns, and orthogonality of dyke trends with the structural grain of enclosing host rocks. Geological observations suggest that sub-horizontal magma flow is a common feature of dyke intrusion and thus changes in petrology, geochemistry and the orientation of flow-induced fabric along the length of a swarm might be expected which would have important bearing on problems concerning location of magma sources and the process of dyke injection.